Preparation method of polyimide battery separator and lithium battery
In the preparation of polyimide battery separators, the penetration and diffusion rate of 1-methyl-2 pyrrolidone is blocked by using surfactant to inhibit the formation of finger-like pores, and the sponge pore-like membrane is prepared by droplet super-spreading method, which solves the problem of current In the art, there are problems such as large thickness of the diaphragm, uneven pore size and long preparation time, which improves the uniformity and performance of the film.
Patent Information
- Application Number
- CN202410505393.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-04-25
AI Technical Summary
Among the existing preparation methods of polyimide battery separators, the film prepared by electrospinning is large in thickness and the pore size distribution is uneven. The template method requires 24 hours solidification bath time, and pore-generating agent is required to be introduced to improve performance. The microstructure of the dip super spreading technology is not uniform enough.
By mixing 1-methyl-2 pyrrolidone, surfactant and water to form a solidification bath, blocking the penetration and diffusion rate of 1-methyl-2 pyrrolidone in the polyamic acid solution, inhibiting the formation of finger-like pores, and using droplet ultrasound Spreading method to prepare sponge-hole polyimide battery separators.
The structural uniformity of the polyimide battery separator is achieved, which reduces the preparation time, avoids the need for using pore-generating agents, and improves the mechanical and electrochemical properties of the membrane.
Smart Images

Figure CN118507980B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high molecular polymer film packaging, and in particular to a method for preparing a polyimide battery separator and a lithium battery. Background Art
[0002] Battery separator refers to a layer of separator material set between the positive and negative electrodes of the battery. It is a very critical part of the battery and has a direct impact on the safety and cost of the battery. Its main function is to isolate the positive and negative electrodes and prevent the electrons in the battery from passing freely, allowing the ions in the electrolyte to pass freely between the positive and negative electrodes. Polyimide (PI) is a class of compounds with imide rings in the molecular chain. It has excellent high temperature resistance, chemical corrosion resistance, electrical insulation, etc., and has broad application prospects in industry. In addition, the presence of polar groups on polyimide can also increase the wettability of the electrolyte, making it more conducive to the transmission of lithium ions when used as a lithium-ion battery separator, and promoting the battery's charge and discharge cycle process.
[0003] At present, the preparation of PI membrane (PI battery membrane) mainly includes electrospinning, template method and droplet super-spreading film method. For PI battery membrane prepared by electrospinning, it mainly relies on the winding and bonding of PI fibers on the substrate to obtain a porous film. The film prepared in this way is thicker, has uneven pore size distribution and poor mechanical properties. In order to solve this problem, it is mostly necessary to introduce other materials to crosslink with it to improve its performance, such as crosslinking it with cellulose to form a hydrogen bond crosslinking structure, thereby improving the uniformity of the internal pore structure of the film, promoting ion transmission and improving its mechanical properties; the template method based on non-solvent induced phase separation is also a common method for preparing PI membranes. For example, after synthesizing a polyimide solution, it is scraped to obtain a PI gel, and then immersed in a non-solvent and solvent mixed coagulation bath to obtain a porous membrane with uniform porosity, high temperature resistance and excellent electrochemical performance. The disadvantage of this method is that during the preparation process, it takes 24 hours to immerse in the coagulation bath to exchange the solvent and non-solvent to obtain a membrane with a uniformly distributed pore structure. In addition, PI porous films can be prepared by introducing other porogens, such as preparing a polyimide-polylactide homogeneous mixed solution, and removing polylactide at 280°C after scraping to obtain a mesoporous polyimide battery separator. The uniform distribution of polylactide makes the mesopores inside the separator uniformly distributed, which helps the uniform transportation of lithium ions and is more conducive to the long-term cycle stability of the battery. Lithium bromide can also be used as a porogen, and after scraping to form a film, it is washed and removed by water to obtain a porous PI separator. The uniformly distributed porogen makes the pores inside the separator uniformly distributed, which can effectively inhibit the appearance of lithium dendrites. Adding porogens to prepare porous films is also a common method in domestic and foreign research. Choosing a suitable porogen can effectively prepare a uniform porous film. For the PI separator prepared by the recent droplet super-spreading technology, it still has a microstructure of finger-like pores, and its structure needs to be further regulated to improve the uniformity of its microstructure. Summary of the invention
[0004] In view of this, the present invention proposes a method for preparing a polyimide battery separator and a lithium battery. Since the surfactant blocks the penetration and diffusion rate of 1-methyl-2-pyrrolidone (NMP), the formation of finger-like pores is inhibited, thereby forming a sponge-like polyimide battery separator with high structural uniformity.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The present invention provides a method for preparing a polyimide battery separator, comprising the following steps:
[0007] S100, mixing hexafluorodianhydride, 4,4'-diaminodiphenyl ether and 1-methyl-2-pyrrolidone to obtain a polyamic acid solution;
[0008] S200, mixing 1-methyl-2-pyrrolidone, a surfactant and water to obtain a coagulation bath;
[0009] S300, spreading the polyamic acid solution on the coagulation bath to obtain a polyamic acid film;
[0010] S400, heating the polyamic acid film to obtain a polyimide battery separator.
[0011] In the above technical scheme, a coagulation bath is configured by mixing 1-methyl-2-pyrrolidone, a surfactant and water, wherein the surfactant is located on the surface of the coagulation bath to form a barrier layer, wherein the added surfactant has a hydrophilic group and a lipophilic group, wherein the lipophilic group of the surfactant faces outward and the hydrophilic group faces downward, and when the polyamic acid solution contacts the lipophilic end, since the 1-methyl-2-pyrrolidone (NMP) in the polyamic acid solution is miscible with water and exhibits lipophobicity, the NMP in the polyamic acid solution, driven by the concentration difference between the coagulation bath and the NMP in the polyamic acid solution, generates a driving force for penetration into the coagulation bath which is blocked by the lipophilic end in the barrier layer, thereby significantly slowing down the penetration and diffusion rate of NMP. According to the research paper titled “Superspreading-based fabrication of thermostable nanoporous polyimidemembranes for high safety separators of lithium-ion batteries” and published in the journal “Small” by Huang Xinxu et al., with DOI “10.1002 / smll.202311219”, there is a finger-like pore structure inside the PI membrane. This finger-like pore structure is caused by the fact that the organic solvent NMP in the PI polymer solution penetrates into the NMP / H2O mixed coagulation bath too quickly. It can be concluded that in the present invention, the surfactant blocks the penetration and diffusion rate of NMP, thereby inhibiting the formation of finger-like pores, thereby forming a sponge-like polyimide battery separator with higher structural uniformity.
[0012] Although the prior art discloses that surfactants induce polylactic acid (PLA) to self-assemble to form a highly regular honeycomb-shaped ordered porous film, the cationic surfactant dodecyltrimethylammonium chloride (DTAC) and the nonionic surfactant 2,4,6-tris(N,N-dimethyl-1,3-propylenediamino)-1,3,5-triazine (MET) are used together to act on polylactic acid (PLA) to induce PLA self-assembly to form a honeycomb-shaped ordered porous film, while the present invention uses a droplet super-spreading film-making method, adding a surfactant to the coagulation bath to block the penetration and diffusion rate of NMP, thereby inhibiting the formation of finger-like pores, forming a sponge-shaped polyimide battery separator with high structural uniformity. The two are completely different in their mechanism of action.
[0013] The purpose of heating in step S400 is to cause the polyamic acid molecular chain to undergo cyclization and dehydration to generate an imide ring structure, thereby obtaining a polyimide (PI) film. It should be noted that, preferably, in order to allow hexafluorodianhydride and 4,4'-diaminodiphenyl ether to fully react, the molar ratio of hexafluorodianhydride to 4,4'-diaminodiphenyl ether is 1:1, and when preparing a coagulation bath, preferably, the mass ratio of 1-methyl-2-pyrrolidone to water is 40:60.
[0014] On the basis of the above technical solution, preferably, the surfactant includes sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or sodium stearate.
[0015] On the basis of the above technical scheme, preferably, the mass fraction of the surfactant in the coagulation bath is 1-5%. The present application does not limit its specific content, for example, it can be 1%, 2%, 3% or 5%. When the mass fraction of the surfactant is too low, the surface activity has a small effect on the penetration rate of the organic solvent NMP, and the NMP penetration rate is not significantly slowed down, resulting in the film finally having a finger-like pore structure; when the mass fraction of the surfactant is too high, the lipophilic end in the barrier layer has an excessively high barrier efficiency for the penetration and diffusion of NMP into the coagulation bath, and the diffusion of NMP in the polyamic acid solution is severely hindered, making it impossible to promote the polyamic acid phase to solidify into a film.
[0016] Based on the above technical solution, preferably, in step S100, 1-methyl-2-pyrrolidone and 4,4'-diaminodiphenyl ether are first mixed, and then hexafluorodianhydride is added to mix to obtain a polyamic acid solution. In this technical solution, the reaction container can be a three-necked flask.
[0017] On the basis of the above technical solution, preferably, in step S100, the temperature of 1-methyl-2-pyrrolidone and 4,4'-diaminodiphenyl ether when mixed is 20-30°C, and a water bath can be used to heat them.
[0018] On the basis of the above technical solution, preferably, in step S100, hexafluorodianhydride, 4,4'-diaminodiphenyl ether and 1-methyl-2-pyrrolidone are mixed and stirred for 18-22 hours under a nitrogen atmosphere to obtain a polyamic acid solution.
[0019] On the basis of the above technical scheme, preferably, in step S100, in the obtained polyamic acid solution, the mass fraction of polyamic acid is 10-18%, and its specific mass fraction is not limited. For example, the mass fraction of the polyamic acid can be 10%, 12%, 15%, 18%, etc. When it is higher than 18%, the fluidity of the solution is too poor to spread and it is not easy to form a film. When it is lower than 10%, the solvent diffusion rate is high and finger-like pores will exist in the formed film.
[0020] Preferably, in step S300, the polyamic acid solution is dripped onto the coagulation bath using a rubber-tipped dropper at 24-26°C.
[0021] Preferably, in step S400, the polyamic acid film is heated at 100°C, 200°C and 300°C for 1-2 hours respectively to obtain a polyimide battery separator, so as to make the polyamic acid molecular chain undergo cyclization and dehydration to form an imide ring structure, thereby obtaining a polyimide battery separator.
[0022] The present invention also provides a lithium battery, which comprises the polyimide battery separator obtained by the preparation method.
[0023] The preparation method of a polyimide battery separator and a lithium battery of the present invention have the following beneficial effects compared with the prior art:
[0024] (1) The present invention configures a coagulation bath by mixing 1-methyl-2-pyrrolidone, a surfactant and water, wherein the surfactant is located on the surface of the coagulation bath to form a barrier layer, wherein the added surfactant has a hydrophilic group and a lipophilic group, wherein the lipophilic group of the surfactant faces outward and the hydrophilic group faces downward. When the polyamic acid solution contacts the lipophilic end, since the 1-methyl-2-pyrrolidone (NMP) in the polyamic acid solution is miscible with water and exhibits lipophobicity, the NMP in the polyamic acid solution, driven by the concentration difference between the coagulation bath and the NMP in the polyamic acid solution, generates a driving force for penetration into the coagulation bath which is blocked by the lipophilic end in the barrier layer, thereby significantly slowing down the penetration and diffusion rate of NMP. Since the surfactant blocks the penetration and diffusion rate of NMP, the formation of finger-like pores is suppressed, thereby forming a sponge-like polyimide battery separator with high structural uniformity.
[0025] (2) The mass fraction of the surfactant in the coagulation bath of the present invention is 1-5%. When the mass fraction of the surfactant is too low, the surface activity has little effect on the penetration rate of the organic solvent NMP, and the NMP penetration rate is not significantly slowed down, resulting in the film finally having a finger-like pore structure. When the mass fraction of the surfactant is too high, the lipophilic end in the barrier layer has too high an efficiency in blocking the penetration and diffusion of NMP into the coagulation bath, and the diffusion of NMP in the polyamic acid solution is severely hindered, making it impossible to promote the solidification of the polyamic acid phase into a film. Only when the mass fraction is 1-5%, the polyimide battery separator will form a sponge pore with high structural uniformity.
[0026] (3) In the polyamic acid solution of the present invention, the mass fraction of polyamic acid is 10-18%. When it is higher than 18%, the fluidity of the solution is too poor to spread and it is not easy to form a film. When it is lower than 10%, the solvent diffusion rate is high and finger-like holes will exist in the formed film. Only when the mass fraction is 10-18%, the polyimide battery separator will form a sponge-like pore with high structural uniformity.
[0027] (4) The PI battery separator prepared in some technologies requires the use of a pore-forming agent to obtain a uniform porous structure. The PI battery separator prepared in the present invention does not require an additional pore-forming agent and can quickly prepare a sponge-like porous PI battery separator with a uniformly distributed pore structure. Compared with the existing technology, the operation is simpler and more convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 The cross-sectional scanning electron microscope (SEM) images of the PI battery separators of Comparative Examples 3-5 provided by the present invention;
[0030] Figure 2 The cross-sectional scanning electron microscope (SEM) images of the PI battery separators of Examples 1 and 7-8 provided by the present invention;
[0031] Figure 3 A histogram of the porosity of the PI battery separators of Example 1, Examples 7-8 and Comparative Examples 3-5 provided by the present invention;
[0032] Figure 4 The pore size distribution diagram of the PI battery separators of Example 1, Examples 7-8 and Comparative Examples 3-5 provided by the present invention;
[0033] Figure 5 The stress-strain curves of the PI battery separators of Comparative Examples 3-5 provided by the present invention;
[0034] Figure 6 The stress-strain curves of the PI battery separators of Examples 1 and 7-8 provided by the present invention;
[0035] Figure 7 The cross-sectional SEM image of the PI battery separator of Comparative Example 6 provided by the present invention and the film-forming optical images of the PI battery separators of Comparative Example 7 and Example 7;
[0036] Figure 8 The thermal dimensional stability diagrams of the PI battery separators of Comparative Example 4 and Example 7 and the commercial PP battery separators under different temperature treatments provided by the present invention;
[0037] Fig. 9 Thermogravimetric curves and thermomechanical curves of the PI battery separator of Example 7 and Comparative Example 4 provided by the present invention and the commercial PP battery separator;
[0038] Fig.10 A cycle performance diagram of a lithium battery assembled with the PI battery separator of Comparative Example 4 provided by the present invention at a temperature of 24-26° C.;
[0039] Fig.11 A cycle performance diagram of a lithium battery assembled with the PI battery separator of Example 7 provided by the present invention at a temperature of 24-26° C.;
[0040] Fig.12 A cross-sectional scanning electron microscope (SEM) image of the PI battery separator of Examples 9-10 provided by the present invention;
[0041] Fig.13 This is a diagram showing the mechanism of action of the surfactant provided by the present invention. DETAILED DESCRIPTION
[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] A method for preparing a polyimide battery separator specifically comprises the following steps:
[0045] 1) 50 mL of NMP solution was added to a three-necked flask, and the three-necked flask was placed in a constant temperature water bath at 20° C. 1.73 g of 4,4'-diaminodiphenyl ether (ODA) was weighed and added to the three-necked flask and stirred to dissolve. After dissolution, 3.83 g of hexafluorodianhydride (6FDA) was added, and then nitrogen was introduced and stirred for 20 h under a nitrogen atmosphere to obtain a polyamic acid solution (PAA solution) with a mass fraction of 10%.
[0046] 2) preparing a coagulation bath by mixing NMP and pure water in a mass ratio of 40:60, and adding 1% by mass of sodium dodecyl sulfate to the coagulation bath to form a new coagulation bath, and using a rubber-tipped dropper to draw the PAA solution onto the liquid surface of the coagulation bath at a temperature of 24-26° C., and the PAA solution is spread on the liquid surface of the coagulation bath and solidified into a film.
[0047] 3) The obtained PAA film is kept at 100° C., 200° C., and 300° C. for 1 h each, so that the polyamic acid molecular chain undergoes cyclization and dehydration to form an imide ring structure, thereby obtaining a PI battery separator.
[0048] Example 2
[0049] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 1), 2.53 g of ODA and 5.61 g of 6FDA are added, and a PAA solution with a mass fraction of 14% is prepared.
[0050] Example 3
[0051] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 1), 3.41 g of ODA and 7.57 g of 6FDA are added, and a PAA solution with a mass fraction of 18% is prepared.
[0052] Example 4
[0053] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 2), 2.5% by mass of sodium dodecyl sulfate is additionally added to the coagulation bath.
[0054] Example 5
[0055] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 2), 5% by mass of sodium dodecyl sulfate is additionally added to the coagulation bath.
[0056] Example 6
[0057] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 2), 1% by mass of sodium stearate is additionally added to the coagulation bath.
[0058] Example 7
[0059] A method for preparing a polyimide battery separator, the steps are the same as those of Example 2, except that in step 2), 2.5% by mass of sodium dodecyl sulfate is additionally added to the coagulation bath.
[0060] Example 8
[0061] A method for preparing a polyimide battery separator, the steps are the same as those of Example 3, except that in step 2), 5% by mass of sodium dodecyl sulfate is additionally added to the coagulation bath.
[0062] Example 9
[0063] A method for preparing a polyimide battery separator, the steps are the same as those of Example 2, except that in step 2), 2.5% by mass of sodium dodecylbenzene sulfonate is additionally added to the coagulation bath.
[0064] Example 10
[0065] A method for preparing a polyimide battery separator, the steps are the same as those of Example 2, except that in step 2), 2.5% by mass of sodium stearate is additionally added to the coagulation bath.
[0066] Comparative Example 1
[0067] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 1), 1.54 g of ODA and 3.41 g of 6FDA are added, and a PAA solution with a mass fraction of 9% is prepared.
[0068] Comparative Example 2
[0069] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 1), 3.64 g of ODA and 8.08 g of 6FDA are added, and a PAA solution with a mass fraction of 19% is prepared.
[0070] Comparative Example 3
[0071] A method for preparing a polyimide battery separator, the steps are the same as those of Example 1, except that in step 2), no surfactant is added.
[0072] Comparative Example 4
[0073] A method for preparing a polyimide battery separator, the steps are the same as those of Example 2, except that in step 2), no surfactant is added.
[0074] Comparative Example 5
[0075] A method for preparing a polyimide battery separator, the steps are the same as those of Example 3, except that in step 2), no surfactant is added.
[0076] Comparative Example 6
[0077] A method for preparing a polyimide battery separator, the steps are the same as those of Example 2, except that in step 2), 0.93% by mass of sodium dodecyl sulfate is additionally added to the coagulation bath.
[0078] Comparative Example 7
[0079] A method for preparing a polyimide battery separator, the steps are the same as those of Example 2, except that in step 2), 5.6% by mass of sodium dodecyl sulfate is additionally added to the coagulation bath.
[0080] Performance testing and results
[0081] 1. Observe the microstructure of the PI battery separators prepared in Examples 1-10 and Comparative Examples 1-7, and test the pore size and porosity. See Table 1 for the test results.
[0082] Table 1
[0083]
[0084] Conclusion: Table 1 combined Figure 1 , 2, 3, and 4 show that, by adjusting the content of the surfactant sodium dodecyl sulfate, Examples 1 and 7-8 can achieve the regulation of the sponge-like pores in the PI battery separator, as well as the regulation of the porosity and pore size distribution. Compared with Examples 1 and 7-8, Comparative Examples 3-5 do not add surfactants, and the prepared PI battery separators are finger-like pores, and the pore size distribution and porosity are greater than those prepared in Examples 1 and 7-8. Since the pore size distribution of the PI battery separator with the addition of surfactants is smaller than the pore size distribution of the PI battery separator without the addition, the risk of lithium dendrite puncture is reduced. Example 1-3 regulates the viscosity of the PAA solution (polyamic acid solution) by adjusting the mass ratio, and then 1% sodium dodecyl sulfate is added to the coagulation bath to obtain a PI battery separator with a sponge-like pore structure. Compared with Examples 1-3, Comparative Example 1 has too small a solution mass fraction, resulting in too small a viscosity, and too large a surface tension, resulting in a large difference in surface tension with the coagulation bath, so the finger-like pore structure still exists after 1% sodium dodecyl sulfate is added to the coagulation bath. It is known from Examples 1, 4, and 5 that when the mass fraction of the solution is the same, increasing the content of the surfactant sodium dodecyl sulfate in the coagulation bath also results in a sponge-like PI battery separator. Combining Examples 1 and 6, it can be seen that changing the type of surfactant, replacing sodium dodecyl sulfate with sodium stearate, can also result in a sponge-like PI battery separator. In Comparative Example 2, due to the excessively high mass fraction of the solution, the viscosity is too high and the fluidity is too poor, so it is difficult to be expelled to the surface of the coagulation bath to spread into a film. Table 1 Combining Figure 7 As can be seen from Comparative Example 6, Comparative Example 7 and Example 7, when the content of the surfactant sodium dodecyl sulfate in the coagulation bath is adjusted to be less than 1%, the formation of finger-like pores in the film forming process cannot be suppressed; and when the content of sodium dodecyl sulfate in the coagulation bath is adjusted to be greater than 5%, the PI battery separator cannot be formed normally. Fig.12 It can be seen that after adding sodium dodecylbenzene sulfonate and sodium stearate as surfactants in Examples 9-10, the cross-sectional structure of the prepared PI battery separator is a sponge-like pore structure. Fig.13The action mechanism diagram of the surfactant is shown in the figure. The present invention adopts the droplet super-spreading technology to prepare the PI battery separator. Although the addition of the surfactant will affect the surface tension of the coagulation bath and affect the film-forming process of the PAA polymer solution on the surface of the coagulation bath, the surfactant is located on the surface of the coagulation bath to form a barrier layer, wherein the added surfactant has a hydrophilic group and a lipophilic group, the lipophilic group of the surfactant faces outward, and the hydrophilic group faces downward. When the polyamic acid solution contacts the lipophilic end, since the 1-methyl-2-pyrrolidone (NMP) in the polyamic acid solution is miscible with water and exhibits oleophobicity, the NMP in the polyamic acid solution, driven by the concentration difference between the coagulation bath and the NMP in the polyamic acid solution, the power of penetration into the coagulation bath is blocked by the lipophilic end in the barrier layer, thereby significantly slowing down the penetration and diffusion rate of NMP. Since the surfactant blocks the penetration and diffusion rate of NMP, the formation of finger-like pores is inhibited, forming a sponge-like polyimide battery separator with high structural uniformity. However, when the mass fraction of the surfactant is too low, the surface activity has little effect on the penetration rate of the organic solvent NMP, and the NMP penetration rate is not significantly slowed down, resulting in the film finally having a finger-like pore structure. When the mass fraction of the surfactant is too high, the lipophilic end in the barrier layer has too high a blocking efficiency for the penetration and diffusion of NMP into the coagulation bath, and the diffusion of NMP in the polyamic acid solution is severely hindered, making it impossible to promote the solidification of the polyamic acid phase into a film. Only when the mass fraction is 1-5%, the polyimide battery separator will form a sponge pore with a higher structural uniformity.
[0085] It should be noted that: Figure 1 (a), (b), and (c) are SEM images of PI battery separators prepared in Comparative Example 3, Comparative Example 4, and Comparative Example 5, respectively; Figure 2 (a), (b), and (c) are SEM images of the PI battery separators prepared in Example 1, Example 7, and Example 8, respectively; Fig.12 (a) and (b) are SEM images of the PI battery separators prepared in Example 9 and Example 10, respectively; Figure 7 (a), (b), and (c) are respectively the cross-sectional SEM image of the PI battery separator of comparative example 6, the film-forming optical image of the PI battery separator of comparative example 7, and the film-forming optical image of the PI battery separator of embodiment 7.
[0086] 2. Examples 1-10, Comparative Examples 1-7 and commercial PP battery separators were subjected to conventional tensile strength tests, bending shrinkage temperature tests, thermogravimetric tests and thermomechanical tests. The results are shown in Table 2.
[0087] Table 2
[0088]
[0089]
[0090] in conclusion:
[0091] Combining Table 2 and Figure 5 and Figure 6 It can be seen that the most direct change brought about by the change of the type of microscopic pore structure of the film is the change in tensile strength. The tensile strength of the PI battery separator with a sponge-like structure in the embodiment is increased to more than 40MPa, while the tensile strength of the PI battery separator with a finger-like pore structure in the comparative example is only 34.7MPa at the highest. In addition, the thermal stability of the PI battery separator with a sponge-like structure is also improved relative to that of the PI battery separator with a finger-like pore structure. Because the commercial PP separator is prepared by melt stretching, the tensile strengths in the transverse and longitudinal directions are different. Although the transverse tensile strength is about 100MPa, its longitudinal tensile strength is only 10MPa, and its high temperature resistance is far worse than that of the PI battery separator.
[0092] It should be noted that Figure 5 (a), (b), and (c) are stress-strain curves of PI battery separators containing finger-like pore structures prepared in Comparative Examples 3, 4, and 5, respectively; Figure 6 (a), (b), and (c) are stress-strain curves of the sponge-like pore structure PI battery separators prepared in Example 1, Example 7, and Example 8, respectively.
[0093] Figure 8 Comparative Example 4 is the finger-shaped pore PI battery separator in the figure, and Example 7 is the thermal dimensional stability of the sponge-shaped pore PI battery separator and the commercial PP separator under different temperature treatments. Figure 8 Combined with Table 2, it can be seen that the commercial PP separator will shrink significantly at 150°C and lose its structural stability, while the PI separator still maintains its dimensional integrity at 300°C, indicating that the excellent high temperature resistance of PI makes the thermal dimensional stability of PI battery separator significantly better than that of commercial PP separator. Fig. 9 (a) and (b) are thermogravimetric and thermomechanical curves, respectively. Fig. 9 (a) Fig. 9In (b), the sponge-like pore PI is Example 7, the finger-like pore PI is Comparative Example 4, and the PP is a commercial PP separator. As shown in Figure (a), the mass loss of the PP separator increases rapidly after 430°C, and the quality drops drastically. The mass loss of the sponge-like structured PI separator gradually increases after 500°C, which is much better than that of the PP separator. Although the mass loss of the PI separator containing the finger-like pore structure also gradually increases at around 430°C, the mass loss is much smaller than that of PP. As shown in Figure (b), the PP separator has tensile rupture at around 160°C, while the PI battery separator containing the finger-like pore structure will only begin to show tensile displacement at around 250°C. Moreover, the stability of the sponge-like structured PI battery separator is better than that of the finger-like pore structured PI battery separator, and a more obvious tensile displacement will only occur at 265°C. The above data show that the sponge-like structured PI battery separator has better thermal stability than the finger-like pore structured PI battery separator.
[0094] 3. Characterization of electrochemical properties of thin films
[0095] With lithium iron phosphate (LFP) as the positive electrode, lithium sheet as the negative electrode, and LB-266 as the electrolyte, button cells were assembled, and charge and discharge cycle tests were carried out at a charge and discharge rate of 0.5c at 24-26°C. The electrochemical properties of Example 7 and Comparative Example 4 were compared, and the cycle stability of the assembled batteries was observed. The results are shown in Table 3.
[0096] Table 3
[0097] Group Battery capacity retention rate (%) Coulomb efficiency (%) Example 7 98 99 Comparative Example 4 84.5 98
[0098] Conclusion: Table 3 combined Figure 10-11 It can be seen that the capacity retention rate of the PI battery separator of Comparative Example 4 after 150 battery cycles is 84.5%, and the coulombic efficiency is 98%; the capacity retention rate of Example 7 after 150 battery cycles is 98%, and the coulombic efficiency is about 99%. The cycle stability is significantly better than the cycle stability of the battery assembled with the PI battery separator containing finger-like pores, indicating that the PI separator with a sponge-like pore structure has better electrochemical properties.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyimide battery separator, characterized in that: The following steps are involved: S100, mixing hexafluorodianhydride, 4,4'-diaminodiphenyl ether and 1-methyl-2-pyrrolidone to obtain a polyamic acid solution; in the obtained polyamic acid solution, the mass fraction of the polyamic acid is 10-18%; S200, mixing 1-methyl-2-pyrrolidone, a surfactant and water to obtain a coagulation bath; the surfactant comprises sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or sodium stearate; and the mass fraction of the surfactant in the coagulation bath is 1-5%; S300, spreading the polyamic acid solution on the coagulation bath to obtain a polyamic acid film; S400, heating the polyamic acid film to obtain a polyimide battery separator.
2. The method for preparing a polyimide battery separator according to claim 1, characterized in that: In step S100, 1-methyl-2-pyrrolidone and 4,4'-diaminodiphenyl ether are first mixed, and then hexafluorodianhydride is added and mixed to obtain a polyamic acid solution.
3. The method for preparing a polyimide battery separator according to claim 2, characterized in that: In step S100, the temperature of the mixture of 1-methyl-2-pyrrolidone and 4,4'-diaminodiphenyl ether is 20-30°C.
4. The method for preparing a polyimide battery separator according to claim 2, characterized in that: In step S100, hexafluorodianhydride, 4,4'-diaminodiphenyl ether and 1-methyl-2-pyrrolidone are mixed and stirred for 18-22 hours under a nitrogen atmosphere to obtain a polyamic acid solution.
5. The method for preparing a polyimide battery separator according to claim 1, characterized in that: In step S300, the polyamic acid solution is dripped onto the coagulation bath using a rubber-tipped dropper at 24-26°C.
6. The method for preparing a polyimide battery separator according to claim 1, characterized in that: In step S400, the polyamic acid film is heated at 100°C, 200°C and 300°C for 1-2 hours respectively to obtain a polyimide battery separator.
7. A lithium battery comprising a polyimide battery separator obtained by the preparation method according to any one of claims 1 to 6.
